PERAN MEDIA MASSA DALAM REAKTULISASI KEMAJUAN PERADABAN ISLAM (Analisis Wacana Terhadap Rubrik Mimbar Jumâat di Surat Kabar Harian) - Sri Rizki, Juni Wati (Institut Agama Islam Negeri Padangsidimpuan, 2018)
Newspapers as general media information play a role in process of re-actualizethe advanced of Islamic civilization. History of Muslimâs glory several centuries ago which almost destroyed, now being exhumed and become the actual information in the newspaper. The efforts were made by newspaper was examined by using some theory as follows: agenda setting, discourse analysis and semiotics that also hasfunction as research method. The results of this study indicate that the Islamic civilization is very advanced in science, architecture, food processing technology, medical, state managementand others. Even, some results of Muslim scientistresearch and thought became references for Western scientists in developing studies in various fields. Therefore, efforts to re-actualize the advanced of Islamic civilization are indispensable as a motivation to raise awareness of Muslims that we are intelligent and proggressifpeople .